This action might not be possible to undo. Are you sure you want to continue?

# Transposition of

formulae

In mathematics, engineering and science, formulae are used to relate physical quantities to each

other. They provide rules so that if we know the values of certain quantities, we can calculate

the values of others. In this unit we discuss how formulae can be transposed, or transformed,

or rearranged.

In order to master the techniques explained here it is vital that you undertake plenty of practice

exercises so that they become second nature.

After reading this text, and/or viewing the video tutorial on this topic, you should be able to:

• transpose formulae in order to make other variables the subject of the formula

Contents

1. Introduction 2

2. Solving a simple linear equation 2

3. Transposition of simple formulae 3

4. The formula for the simple pendulum 5

5. Further examples of useful formulae 6

1 c mathcentre June 11, 2004

1. Introduction

Consider the formula for the period, T, of a simple pendulum of length l:

T = 2π

l

g

, where l is the length of the pendulum

Now, on Earth, we tend to regard g, the acceleration due to gravity, as being ﬁxed. It varies a

little with altitude but for most purposes we can regard it as a constant.

Just suppose we had a pendulum of a ﬁxed length l, and we took it somewhere else, say the

moon, or Mars. The gravity there would not be the same and so the value of g would be diﬀerent

from its value on Earth.

Suppose we wanted to measure g. One way would be to take the pendulum, set it swinging and

measure the time, T, for one complete cycle. Once we have measured the time, we could then

use that to calculate g. But before we could do this, we would need to know what g was, in

terms of the rest of the symbols in the formula. So we need to re-arrange the formula so that it

states “g =?”. We will show you how to do this rearrangement later in the video.

To rearrange, transform, or tranpose the formula, we need many of the techniques used to solve

equations. So, the video ‘Solving Linear Equations in One Variable’ might be very useful to

have a look at.

2. Solving a simple linear equation

Before we look at rearranging more complicated formulae we recap by having a look at a simple

linear equation. Suppose we wanted to solve

3x + 5 = 6 −3(5 −2x)

Our aim is to end up with an expression for x, that is ‘x =?’. We start by expanding the

brackets on the right.

3x + 5 = 6 −15 + 6x

3x + 5 = 6x −9

We then proceed to manipulate this to try to get all the terms involving x on to one side. We

must preserve the balance in the original equation by doing exactly the same operations to both

sides.

Subtracting 3x from both sides:

3x −3x + 5 = 6x −3x −9

5 = 3x −9

Adding 9 to both sides:

5 + 9 = 3x −9 + 9

14 = 3x

and so

x =

14

3

We have obtained an expression for x as required.

c mathcentre June 11, 2004 2

With practice the amount of working written down will reduce because you will be able to carry

out many of the stages at the same time. Having gone through the steps of solving an equation,

the same technique, particularly the idea of keeping the balance by doing the same thing to

both sides, is what we are going to do when we look at the transformation of formulae.

3. Transposition of simple formulae

Example

Consider the formula v = u+at. Suppose we wish to transpose this formula to obtain one for t.

Because we want to obtain t on its own we start by subtracting u from each side:

v = u + at

v −u = at

We now divide everything on both sides by a.

v −u

a

=

at

a

= t

and so ﬁnally t =

v −u

a

. We have transposed the formula to ﬁnd an expression for t.

Example

Consider the formula v

2

= u

2

+ 2as and suppose we wish to transpose it to ﬁnd u.

We want to obtain u on its own and so we begin by subtracting 2as from each side.

v

2

= u

2

+ 2as

v

2

−2as = u

2

Finally, taking the square root of both sides:

u =

√

v

2

−2as

Notice we need to take the square root of the whole term (

√

v

2

−2as) in order to ﬁnd u.

Example

Consider the formula s = ut +

1

2

at

2

. Suppose we want to transpose it to ﬁnd a.

Because we want a on its own, we begin by subtracting ut from both sides.

s = ut +

1

2

at

2

s −ut =

1

2

at

2

Multiplying both sides by 2:

2(s −ut) = at

2

Dividing both sides by t

2

:

2(s −ut)

t

2

= a

and so

a =

2(s −ut)

t

2

3 c mathcentre June 11, 2004

Example

Suppose we wish to rearrange y(2x + 1) = x + 1 in order to ﬁnd x.

Notice that x occurs both on the left and on the right. We need to try to get all the terms

involving x together. We begin by expanding the brackets on the left:

y(2x + 1) = x + 1

2xy + y = x + 1

Subtracting x from both sides:

2xy −x + y = 1

The left-hand side now has two terms involving x. We can factorise these as follows:

x(2y −1) + y = 1

Then subtracting y from both sides:

x(2y −1) = 1 −y

and ﬁnally, dividing both sides by (2y −1)

x =

1 −y

2y −1

Example

Suppose we wish to rearrange

y

y + x

+ 5 = x to ﬁnd an expression for y.

We begin by multiplying every term on both sides by (y + x) in order to remove the fractions:

y + 5(y + x) = x(y + x)

Next we multiply out the brackets:

y + 5y + 5x = xy + x

2

We try to get all the terms involving y onto the left-hand side. Subtracting xy from both sides:

6y −xy + 5x = x

2

Subtracting 5x from both sides, and taking out the common factor y we have

y(6 −x) = x

2

−5x

Finally, dividing both sides by 6 −x we obtain

y =

x

2

−5x

(6 −x)

c mathcentre June 11, 2004 4

Exercise 1

Rearrange each of the following formulae to make the quantity shown the subject.

1. v = u + at, u

2. v

2

= u

2

+ 2as, s

3. s = vt −

1

2

at

2

, a

4. p = 2(w + h), h

5. A = 2πr

2

+ 2πrh, h

6. E =

1

2

mv

2

+ mgh, v

7. E =

1

2

mv

2

+ mgh, m

8. a(3b −1) = 2b + 2, b

9.

t

2t −s

= 3s, t

10.

s

2t −s

+ 5 = 3t, s

4. The formula for the simple pendulum

We began with the formula T = 2π

l

g

. Let us now try to rearrange this to ﬁnd an expression

for g.

We begin by squaring both sides of the equation in order to remove the square root.

T

2

= (2π)

2

l

g

To remove the fraction we multiply both sides by g:

T

2

g = (2π)

2

l

Dividing both sides by T

2

gives

g =

(2π)

2

l

T

2

By observing the two square terms on the right, we note that this formula could be written, if

we wish, in the equivalent form

g =

2π

T

2

l

5 c mathcentre June 11, 2004

5. Further examples of useful formulae

Example - the lens formula

The so-called lens formula, which is used in optics, is given by

1

f

=

1

u

+

1

v

Suppose we want to rearrange this formula to ﬁnd u.

Because we want to isolate u we begin by subtracting

1

v

from both sides.

1

f

−

1

v

=

1

u

The left-hand side fractions can be combined by expressing them over a common denominator

v −f

fv

=

1

u

Inverting both sides

fv

v −f

= u

and so u =

fv

v −f

as required.

Example

The formula T =

T

0

1 −

v

2

c

2

1/2

arises in the study of relativity. Suppose we want to rearrange it

to ﬁnd an expression for

v

c

.

We begin by noticing that if we square both sides this will remove the square root term (i.e. the

power

1

2

) on the right-hand side. So squaring:

T

2

=

T

2

0

1 −

v

2

c

2

We remove the fraction by multiplying both sides by

1 −

v

2

c

2

:

T

2

1 −

v

2

c

2

= T

2

0

Dividing both sides by T

2

:

1 −

v

2

c

2

=

T

2

0

T

2

Adding

v

2

c

2

to both sides gives

1 =

T

2

0

T

2

+

v

2

c

2

c mathcentre June 11, 2004 6

Subtracting

T

2

0

T

2

from both sides:

1 −

T

2

0

T

2

=

v

2

c

2

Finally, taking the square root of both sides

v

c

=

1 −

T

2

0

T

2

as required.

Exercise 2

Rearrange each of the following formulae to make the quantity shown the subject.

1. y = a +

1

x

, x

2. y = a +

1

1 −x

, x

3. P =

P

0

1 −r

2

, r

4. m = k

a(1 −x), x

5. V =

V

0

√

r

2

−1

, r

Answers

Exercise 1

1. u = v −at 2. s =

v

2

−u

2

2a

3. a =

2(vt −s)

t

2

4. h =

1

2

(p −2w)

5. h =

A −2πr

2

2πr

6. v =

2(E −mgh)

m

7. m =

2E

v

2

+ 2gh

8. b =

2 + a

3a −2

9. t =

3s

2

6s −1

10. s =

6t

2

−10t

3t −4

.

Exercise 2

1. x =

1

y −a

2. x = 1 −

1

y −a

3. r =

1 −

P

0

P

4. x = 1 −

1

a

m

k

2

5. r =

1 +

V

0

V

2

7 c mathcentre June 11, 2004

So. Subtracting 3x from both sides: 3x − 3x + 5 = 6x − 3x − 9 5 Adding 9 to both sides: = 3x − 9 5 + 9 = 3x − 9 + 9 14 = 3x x= 14 3 We have obtained an expression for x as required. So we need to re-arrange the formula so that it states “g =?”. Introduction Consider the formula for the period. We start by expanding the brackets on the right. on Earth. Suppose we wanted to solve 3x + 5 = 6 − 3(5 − 2x) Our aim is to end up with an expression for x. the video ‘Solving Linear Equations in One Variable’ might be very useful to have a look at. T . that is ‘x =?’. But before we could do this. Just suppose we had a pendulum of a ﬁxed length l. say the moon.1. or Mars. set it swinging and measure the time. It varies a little with altitude but for most purposes we can regard it as a constant. or tranpose the formula. 3x + 5 = 6 − 15 + 6x 3x + 5 = 6x − 9 We then proceed to manipulate this to try to get all the terms involving x on to one side. we could then use that to calculate g. we tend to regard g. The gravity there would not be the same and so the value of g would be diﬀerent from its value on Earth. transform. we would need to know what g was. T . for one complete cycle. One way would be to take the pendulum. as being ﬁxed. in terms of the rest of the symbols in the formula. Suppose we wanted to measure g. To rearrange. Once we have measured the time. 2. We must preserve the balance in the original equation by doing exactly the same operations to both sides. of a simple pendulum of length l: T = 2π l . g where l is the length of the pendulum Now. Solving a simple linear equation Before we look at rearranging more complicated formulae we recap by having a look at a simple linear equation. 2004 and so 2 . and we took it somewhere else. we need many of the techniques used to solve equations. the acceleration due to gravity. We will show you how to do this rearrangement later in the video. c mathcentre June 11.

2004 1 2 at 2 and so 3 . 1 s = ut + at2 2 s − ut = Multiplying both sides by 2: 2(s − ut) = at2 Dividing both sides by t2 : 2(s − ut) =a t2 a= 2(s − ut) t2 c mathcentre June 11. the same technique. Suppose we wish to transpose this formula to obtain one for t.With practice the amount of working written down will reduce because you will be able to carry out many of the stages at the same time. taking the square root of both sides: √ u = v 2 − 2as √ Notice we need to take the square root of the whole term ( v 2 − 2as) in order to ﬁnd u. is what we are going to do when we look at the transformation of formulae. 2 Because we want a on its own. Having gone through the steps of solving an equation. Because we want to obtain t on its own we start by subtracting u from each side: v = u + at v − u = at We now divide everything on both sides by a. we begin by subtracting ut from both sides. at v−u = =t a a v−u and so ﬁnally t = . particularly the idea of keeping the balance by doing the same thing to both sides. Transposition of simple formulae Example Consider the formula v = u + at. Suppose we want to transpose it to ﬁnd a. a Example Consider the formula v 2 = u2 + 2as and suppose we wish to transpose it to ﬁnd u. 3. We have transposed the formula to ﬁnd an expression for t. Example 1 Consider the formula s = ut + at2 . v 2 = u2 + 2as v 2 − 2as = u2 Finally. We want to obtain u on its own and so we begin by subtracting 2as from each side.

We can factorise these as follows: x(2y − 1) + y = 1 Then subtracting y from both sides: x(2y − 1) = 1 − y and ﬁnally. y+x We begin by multiplying every term on both sides by (y + x) in order to remove the fractions: Suppose we wish to rearrange y + 5(y + x) = x(y + x) Next we multiply out the brackets: y + 5y + 5x = xy + x2 We try to get all the terms involving y onto the left-hand side. We need to try to get all the terms involving x together. We begin by expanding the brackets on the left: y(2x + 1) = x + 1 2xy + y = x + 1 Subtracting x from both sides: 2xy − x + y = 1 The left-hand side now has two terms involving x. dividing both sides by (2y − 1) x= Example y + 5 = x to ﬁnd an expression for y. Notice that x occurs both on the left and on the right. 2004 4 . dividing both sides by 6 − x we obtain y= x2 − 5x (6 − x) 1−y 2y − 1 c mathcentre June 11. Subtracting xy from both sides: 6y − xy + 5x = x2 Subtracting 5x from both sides.Example Suppose we wish to rearrange y(2x + 1) = x + 1 in order to ﬁnd x. and taking out the common factor y we have y(6 − x) = x2 − 5x Finally.

2. in the equivalent form 2 2π g= l T g= l g l . + 5 = 3t. t = 3s. T 2 = (2π)2 To remove the fraction we multiply both sides by g: T 2 g = (2π)2 l Dividing both sides by T 2 gives (2π)2 l T2 By observing the two square terms on the right. We begin by squaring both sides of the equation in order to remove the square root. 1 3. p = 2(w + h). 2 4. v 2 = u2 + 2as. v = u + at. u s a h h v m b 5. 2t − s 9. s = vt − at2 . E = mv 2 + mgh. The formula for the simple pendulum We began with the formula T = 2π for g. a(3b − 1) = 2b + 2. t 2t − s s 10. 2 1 7. 2004 . 1. E = mv 2 + mgh. 2 8. 1 6. Let us now try to rearrange this to ﬁnd an expression g 5 c mathcentre June 11. if we wish. we note that this formula could be written. A = 2πr2 + 2πrh. s 4.Exercise 1 Rearrange each of the following formulae to make the quantity shown the subject.

Suppose we want to rearrange it to ﬁnd an expression for v . So squaring: 2 T2 = 2 T0 2 1 − v2 c We remove the fraction by multiplying both sides by 2 1− v2 : c2 T Dividing both sides by T 2 : v2 1− 2 c v2 c2 2 = T0 1− Adding v2 to both sides gives c2 = 2 T0 T2 2 v2 T0 1= 2 + 2 T c c mathcentre June 11. the power 1 ) on the right-hand side.the lens formula The so-called lens formula. v−f arises in the study of relativity. Because we want to isolate u we begin by subtracting 1 1 1 − = f v u The left-hand side fractions can be combined by expressing them over a common denominator v−f 1 = fv u Inverting both sides fv =u v−f and so u = Example The formula T = T0 1− v 2 1/2 c2 1 from both sides. c We begin by noticing that if we square both sides this will remove the square root term (i. Further examples of useful formulae Example . 2004 6 . which is used in optics.e. is given by 1 1 1 = + f u v Suppose we want to rearrange this formula to ﬁnd u.5. v fv as required.

1 − r2 4. r2 − 1 r 2. 1−x P0 . s = . s = v 2 − u2 2a 3. 9. y = a + . v = 2πr m 6t2 − 10t 3s2 10. y = a + 3. x 2. h = a(1 − x). V = √ Answers Exercise 1 1. x = 1 − a k 5. m = 1 4. Exercise 2 2 T0 v2 = 2 T2 c 1− 2 T0 T2 Rearrange each of the following formulae to make the quantity shown the subject. m = k 5. x = 1 − 2 1 y−a 1+ 3. h = (p − 2w) 2 v2 2E + 2gh 8. a = 2(vt − s) t2 7.Subtracting 2 T0 from both sides: T2 1− Finally. u = v − at 5. 2004 . taking the square root of both sides v = c as required. x = 1 y−a 2. r = V0 V 2 1− P0 P 1 m 4. P = x x r x 1 . r = 7 c mathcentre June 11. b = 2+a 3a − 2 2(E − mgh) A − 2πr2 6. t = 6s − 1 3t − 4 Exercise 2 1. V0 . 1 1.